The Role of Mcl-1 in S. aureus-Induced Cytoprotection of Infected Macrophages. (28th January 2013) - Koziel, Joanna; Kmiecik, Katarzyna; Chmiest, Daniela; Maresz, Katarzyna; Mizgalska, Danuta; Maciag-Gudowska, Agnieszka; Mydel, Piotr; Potempa, Jan
Abstract : As a facultative intracellular pathogen, Staphylococcus aureus invades macrophages and then promotes the cytoprotection of infected cells thus stabilizing safe niche for silent persistence. This process occurs through the upregulation of crucial antiapoptotic genes, in particular, myeloid cell leukemia-1 (MCL-1) . Here, we investigated the underlying mechanism and signal transduction pathways leading to increased MCL-1 expression in infected macrophages. Live S. aureus not only stimulated de novo synthesis of Mcl-1, but also prolonged the stability of this antiapoptotic protein. Consistent with this, we proved a crucial role of Mcl-1 in S. aureus -induced cytoprotection, since silencing of MCL1 by siRNA profoundly reversed the cytoprotection of infected cells leading to apoptosis. Increased MCL1 expression in infected cells was associated with enhanced NFκ B activation and subsequent IL-6 secretion, since the inhibition of both NFκ B and IL-6 signalling pathways abrogated Mcl-1 induction and cytoprotection. Finally, we confirmed our observation in vivo in murine model of septic arthritis showing the association between the severity of arthritis and Mcl-1 expression. Therefore, we propose that S. aureus is hijacking the Mcl-1-dependent inhibition of apoptosis to prevent the elimination of infected host cells, thus allowing the intracellular persistence of the pathogen, its dissemination by infected macrophages, and the progression of staphylococci diseases.